2002
DOI: 10.1023/a:1021462012442
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The TFCs effectively delivered therapeutically efficacious amounts of sCT across the buccal mucosa in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…While gels represent the most common oral delivery strategy, oral rinses (6), local injections (26), and mucoadhesive patches (21,22) are also frequently used. Due to the lack of compatibility, it is challenging to formulate poorly water soluble and/or unstable compounds, such as fenretinide, in topical aqueous-based delivery vehicles (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While gels represent the most common oral delivery strategy, oral rinses (6), local injections (26), and mucoadhesive patches (21,22) are also frequently used. Due to the lack of compatibility, it is challenging to formulate poorly water soluble and/or unstable compounds, such as fenretinide, in topical aqueous-based delivery vehicles (27).…”
Section: Discussionmentioning
confidence: 99%
“…Mucoadhesive bi-layer thin-film composites (TFC) were formulated as described in our previous reports (21,22). The TFCs were cut with a circular arch punch to a diameter of 7 cm and subsequently trimmed with a scalpel to the corresponding oral explant size.…”
Section: Methodsmentioning
confidence: 99%
“…1. The mucous gelatinous layer (1) covers the epithelium (2), beneath which lies the connective-tissue lamina propria (3), which has an abundant supply of blood and lymph vessels; beneath this is a thin layer of smooth-muscle tissue (4). The thickness of the mucus layer varies in different mucosal tissue surfaces from 50 to 500 mm in the stomach and to less than 1 mm in the oral cavity [5 -7, 19].…”
Section: Structure and Function Of Mucous Membranesmentioning
confidence: 99%
“…Two-layer films consisting of mucoadhesive and protective layers and containing oxytocin [61], testosterone [62], and the Russian agent Trinitrolong [63], are examples of buccal mucoadhesive films with systemic actions. In vivo studies of films containing calcitonin (in rabbits) demonstrated that therapeutic doses of calcitonin (a peptide hormone agent) can be delivered via the buccal route [2].…”
Section: The Main Types Of Mucoadhesive Dds: Advantages and Disadvantmentioning
confidence: 99%
See 1 more Smart Citation